Micro-crosslinking structure interlocking type fluid loss agent, preparation method thereof and well cementation cement slurry system
By introducing micro-crosslinked structure interlocking network polymers into the water loss reduction agent, the problems of uncontrollable water loss and reduced mechanical strength in the water loss reduction agent in the prior art under ultra-high temperature and ultra-high pressure environment are solved, and the stability and mechanical properties of the cement slurry system have been significantly improved.
Patent Information
- Application Number
- CN202411745103.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing water loss reducing agents exhibit uncontrollable water loss, "inverted" of cement slurry thickening time and reduced mechanical strength in ultra-high temperature and ultra-high pressure environments, making it difficult to meet the complex performance requirements of cement slurry in ultra-deep and deep wells.
A micro-crosslinked structural interlocking water-reducing agent is used to introduce reactive active points of "triple double bonds" or "four double bonds" to form a structural interlocking rigid network-like polymer, which improves temperature, pressure, and salt resistance, and optimizes water-reducing performance through synergistic monomers, crosslinking agents and regulators.
The settlement stability and mechanical properties of the cement slurry system are significantly improved, and the comprehensive performance is ensured within the temperature range of 20-245℃ is avoided, which is to avoid the problem of "inverted" in the thickening time of the cement slurry and the reduction of mechanical strength.
Smart Images

Figure CN119798535A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a micro-crosslinked structure interlocking type fluid loss reducer and a preparation method thereof and a cementing slurry system, belonging to the technical field of oil and gas well cementing. Background Art
[0002] Deep and ultra-deep oil and gas resources have great potential and have become an important area for increasing oil and gas reserves and production, and are gradually shifting to ultra-deep layers. At present, ultra-deep and ultra-deep oil and gas drilling technology has achieved leapfrog development. The 7,000m well depth has matured, breaking through the 8,000m level and gradually becoming normalized, stepping onto the 9,000m level, and crossing the 10,000m level. Cementing slurry technology is the key to ensuring the safety of cementing operations in deep and ultra-deep wells, achieving long-term and efficient sealing of cement rings, and supporting safe oil and gas production. It runs through the entire life cycle of oil and gas well drilling, completion, production, and abandonment. However, cementing of ultra-deep and ultra-deep oil and gas wells faces complex geological and extreme working conditions such as ultra-depth (>9000m), ultra-high temperature (>200℃), and ultra-high pressure (>140MPa), which poses great challenges to the key materials and systems of cementing slurry. Fluid loss reducer is one of the core main agents of oil well cement slurry. It plays a vital role in reducing the water loss of cement slurry, ensuring the stability of the system, and preventing cement slurry from filtering out to the formation and polluting the reservoir.
[0003] There are many types of fluid loss reducers, among which 2-acrylamido-2-methylpropanesulfonic acid (AMPS) copolymers have become a hot topic in research and application due to their excellent molecular structure designability, temperature and salt resistance, and strong adaptability. However, under harsh environments such as ultra-high temperature and ultra-high pressure, AMPS copolymer fluid loss reducers still have some problems: ① Under ultra-high temperature and strong alkaline conditions, the polymer molecular structure is prone to conformational changes, partial hydrolysis chain scission, and adsorption-desorption imbalance, resulting in uncontrollable water loss of cement slurry and deterioration of comprehensive performance; ② Fluid loss reducers are often linear polymers with obvious high-temperature dilution characteristics, and the sedimentation stability of cement slurry deteriorates under ultra-high temperatures, affecting cementing construction safety and sealing quality; ③ Poor adaptability in a wide temperature range, making it difficult to meet the requirements for cement slurry rheology, stability, and mechanical strength development in ultra-deep and ultra-deep well cementing, such as long injection and replacement stroke of cement slurry, large friction resistance of small gaps in tail pipes, and large temperature difference between the top and bottom of the effective sealing section across the temperature zone. Therefore, it is urgent to develop high-performance fluid loss reducers suitable for ultra-deep and extra-deep well cementing to improve the comprehensive performance of the cement slurry system and meet the technical requirements of cementing in complex wells.
[0004] CN109503782A discloses an inorganic-organic polymer fluid loss reducer, which is grafted copolymerized with itaconic acid, acrylamide monomers, AMPS, silane coupling agent and inorganic materials (one of silicon carbide, silicon dioxide and alumina), etc. It introduces inorganic non-metallic particles and micro-crosslinked structures of modified polymers on the basis of existing polymers, thereby improving the temperature resistance of the fluid loss reducer, and controlling the water loss of cement slurry within 60mL at 230°C. However, the water loss reduction effect above 230°C is not described, and the effect on other properties of cement slurry is not investigated.
[0005] CN106188395A discloses a micro-cross-linked structure, high temperature and salt resistant cementing slurry fluid loss reducer, which is prepared by free radical aqueous solution polymerization of AMPS, acrylamide (AM), unsaturated polycarboxylic acid, N-vinyl pyrrolidone (NVP) and N, N-methylenebisacrylamide (cross-linking agent), etc., with an applicable temperature of 30-240°C, resistance to saturated brine, and cement slurry API water loss of less than 50mL. However, the polymer molecular structure contains more than 15% acrylamide by mass, and its amide group is hydrolyzed into a carboxylic acid group with a strong retarding effect under high temperature and strong alkaline conditions. Although the water loss reduction ability is improved, it is easy to cause adverse effects such as "inverted" thickening time of cement slurry and reduced compressive strength of cement stone, thereby affecting the comprehensive performance of the cement slurry system.
[0006] Although the polymer fluid loss reducers disclosed in the above prior art have improved heat and salt resistance, they still have certain defects in comprehensive performance, especially in ultra-deep and ultra-deep well cementing at ultra-high temperature. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a micro-crosslinked interlocking fluid loss agent and its preparation method and cementing cement slurry system. The fluid loss agent of the present invention has better temperature and salt resistance, better fluid loss reduction performance, and can improve the sedimentation stability of the cement slurry system, while having no adverse effect on the comprehensive performance of the cement slurry system.
[0008] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a micro-crosslinked interlocking fluid loss additive, which comprises the following steps:
[0009] (1) 30-90 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid, 3-20 parts by weight of a carboxylic acid or its derivative monomer containing a vinyl group, and water are mixed, and a pH adjuster is added to adjust the pH value of the system to 6-7; 5-30 parts by weight of a modified acrylamide monomer, 2-30 parts by weight of a vinyl cyclic monomer, and 0.1-3 parts by weight of a crosslinking agent are added, wherein the crosslinking agent includes a compound containing three alkenyl groups or four alkenyl groups; and then 0.02-3 parts by weight of a molecular weight regulator, 0.05-2 parts by weight of a chelating agent, and 0.2-1 parts by weight of an oxidant are added to obtain a mixed system;
[0010] (2) adding an aqueous solution containing 0.2-1 parts by weight of a reducing agent dropwise into the mixed system, and reacting for a period of time after the addition is completed to obtain the micro-crosslinked interlocking fluid loss additive.
[0011] According to a specific embodiment of the present invention, preferably, the weight ratio of the 2-acrylamido-2-methylpropanesulfonic acid, the vinyl-containing carboxylic acid or its derivative monomer, the modified acrylamide monomer, the vinyl cyclic monomer, the cross-linking agent, the molecular weight regulator, the chelating agent, the oxidant and the reducing agent is (37-74): (5-15): (15-28): (5-20): (0.5-2): (0.05-3): (0.05-1.5): (0.3-1): (0.23-0.56).
[0012] According to a specific embodiment of the present invention, preferably, in step (1), the vinyl-containing carboxylic acid or its derivative monomer comprises one or more of acrylic acid, itaconic acid, maleic anhydride, maleic acid and fumaric acid.
[0013] According to a specific embodiment of the present invention, preferably, in step (1), based on 30-90 parts by weight of 2-acrylamido-2-methylpropanesulfonic acid, the amount of water used is 230-850 parts by weight.
[0014] According to a specific embodiment of the present invention, preferably, in step (1), the pH adjuster includes alkaline compounds such as sodium hydroxide and / or potassium hydroxide.
[0015] According to a specific embodiment of the present invention, preferably, in step (1), the modified acrylamide monomer includes one or more of N-n-butoxymethyl acrylamide, N,N-diethyl acrylamide, N-hydroxyethyl acrylamide, diacetone acrylamide and N-isopropyl acrylamide.
[0016] According to a specific embodiment of the present invention, preferably, in step (1), the vinyl cyclic monomer includes one or more of N-vinyl pyrrolidone, N-vinyl caprolactam and vinyl cyclopentane.
[0017] According to a specific embodiment of the present invention, preferably, in step (1), the cross-linking agent includes one or two of triallylamine and pentaerythritol tetraallyl ether.
[0018] According to a specific embodiment of the present invention, preferably, in step (1), the molecular weight regulator includes one or more of mercaptopropionic acid, mercaptoethanol, isopropanol, dodecanethiol, hydroquinone and 2-mercaptobenzoic acid.
[0019] According to a specific embodiment of the present invention, preferably, in step (1), the chelating agent includes one or more of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate and diethylenetriaminepentaacetic acid.
[0020] According to a specific embodiment of the present invention, preferably, in step (1), the oxidant includes one or more of ammonium persulfate, potassium persulfate, azobisisobutylimidazoline hydrochloride, azobisisobutylamidine hydrochloride, hydrogen peroxide, benzoyl peroxide and isopropylbenzene hydroperoxide.
[0021] According to a specific embodiment of the present invention, preferably, in step (2), before the aqueous solution containing 0.2-1 parts by weight of the reducing agent is added dropwise to the mixed system, the method further comprises: heating the mixed system to 30-60° C. under stirring conditions of 150±50 rpm.
[0022] According to a specific embodiment of the present invention, preferably, in step (2), the reducing agent includes one or more of sodium sulfite, sodium bisulfite, ferrous sulfate, ferrous chloride, N,N-dimethylaniline and sodium dithionite.
[0023] According to a specific embodiment of the present invention, preferably, in step (2), the mass concentration of the reducing agent in the aqueous solution containing 0.2-1 parts by weight of the reducing agent is 0.4-2%.
[0024] According to a specific embodiment of the present invention, preferably, in step (2), the dripping time is 30-60 min, and the temperature of the mixing system during the dripping process is 30-60°C.
[0025] According to a specific embodiment of the present invention, preferably, in step (2), the reaction temperature is 60-90° C., and the reaction time is 1-6 h.
[0026] The second aspect of the present invention provides a micro-crosslinked structure interlocking type fluid loss additive, which is prepared by the above-mentioned preparation method of the micro-crosslinked structure interlocking type fluid loss additive.
[0027] A third aspect of the present invention provides a cementing slurry system, which comprises at least cement and the above-mentioned micro-crosslinked structure interlocking fluid loss additive.
[0028] According to a specific embodiment of the present invention, preferably, the cementing slurry system comprises: 100 parts by weight of cement, 3-5 parts by weight of the micro-crosslinked structure interlocking fluid loss reducer, 0-80 parts by weight of quartz sand, 0-6 parts by weight of stabilizer, 0-3 parts by weight of dispersant, 0-6 parts by weight of retarder, 0-0.5 parts by weight of defoamer, 0-15 parts by weight of high temperature strength decline inhibitor and 40-70 parts by weight of water. More preferably, the particle size of the quartz sand is 200-600 meshes.
[0029] According to a specific embodiment of the present invention, preferably, the density of the cementing slurry system is 1.90±0.02 g / cm 3 .
[0030] According to a specific embodiment of the present invention, the cement includes G-grade oil well cement. The stabilizer, dispersant, retarder and defoamer can all be products in the prior art. Specifically, the stabilizer can include a biopolymer high temperature stabilizer, an acrylamide polymer ultra-high temperature suspension stabilizer, etc., such as one or two of a high temperature stabilizer DRK-3S and an ultra-high temperature suspension stabilizer DRK-4L. The dispersant can include an aldehyde ketone condensation polymer dispersant and / or a polystyrene sulfonate dispersant, such as one or more of a dispersant DRS-1S, a dispersant SAF, a dispersant SXY, a dispersant USZ and a dispersant SDJZ-1. The high temperature retarder can include an acrylamide polymer retarder and / or a 2-acrylamide-2-methylpropane sulfonic acid polymer retarder, such as one or more of a retarder DRH-2L, a retarder DRH-3L, a retarder JXH-2L and a retarder HX-36L. The defoamer may include one or more of organic esters, polyoxypropylene glycerol ether, and polydimethylsiloxane, such as defoamer DRX-1L, etc. The high temperature strength decay inhibitor may include mineral powder, such as high temperature strength decay inhibitor DRB-3S.
[0031] The present invention has at least the following beneficial effects:
[0032] The present invention adopts micro-crosslinking polymerization technology to introduce "three double bonds" or "four double bonds" reactive active points into the polymer molecular structure, and forms a structurally interlocked rigid network polymer through chemical bond linkage, and through the synergistic effect between each monomer, crosslinking agent, molecular weight regulator and chelating agent, the heat, pressure and salt resistance of the fluid loss reducer of the present invention are greatly improved, and the water loss reduction performance is excellent, and the sedimentation stability of the cement slurry system and the mechanical properties of cement stone under ultra-high temperature conditions can be significantly improved. At the same time, the fluid loss reducer of the present invention has basically no adverse effect on the thickening performance of the cement slurry system, and the thickening curve is normal. Moreover, the fluid loss reducer of the present invention has a wide applicable temperature range, and is applicable in the temperature range of 20-245°C, and has no adverse effect on the comprehensive performance of the cement slurry system in this temperature range. In addition, the preparation method of the fluid loss reducer of the present invention is simple, the conditions are mild, and it can be mass-produced and promoted. The fluid loss reducer of the present invention can be applied to various cementing slurry systems of conventional density, low density and high density at medium temperature, high temperature and ultra-high temperature, and can meet the cementing technology requirements under complex working conditions such as deep wells, ultra-deep wells, extra-deep wells, high-pressure gas wells, unconventional oil and gas wells, gas storage wells and geothermal wells, and has a broad application market. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The effect of different curing times on the API water loss of cement slurry systems containing 5% of the fluid loss reducer prepared in Example 1 and 5% of the fluid loss reducer prepared in Comparative Example 1 at 245°C and 130 MPa is shown.
[0034] Figure 2 The effect of different salt concentrations on the API water loss of the cement slurry system mixed with the fluid loss reducer prepared in Example 1 under the conditions of 245°C and 130 MPa is shown.
[0035] Figure 3 The thickening curve of the cement slurry system containing 4% of the fluid loss reducer prepared in Example 1 at 245° C. and 130 MPa is shown. DETAILED DESCRIPTION
[0036] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the present invention is now described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.
[0037] It should be noted that, unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.
[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0039] It should be understood that the terms "comprises," "comprising," and / or "containing" when used herein specify the presence of stated features, integers, steps, components, or combinations thereof, but do not preclude the presence or addition of one or more other features, integers, steps, components, or combinations thereof.
[0040] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in the present invention.
[0041] Example 1
[0042] 74 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of maleic anhydride and 4 g of acrylic acid were weighed and dissolved in 350 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 15 g of N-n-butoxymethyl acrylamide, 5 g of N-vinyl pyrrolidone and 1 g of triallylamine were added and mixed evenly; 0.05 g of mercaptopropionic acid, 0.05 g of disodium ethylenediaminetetraacetate and 0.5 g of ammonium persulfate were then added to obtain a mixed system; the mixed system was heated to 45° C. under stirring conditions of 200 rpm, and 0.23 g of sodium bisulfite was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 45° C. over 30 minutes. After the addition was completed, the temperature was slowly raised to 70° C. and the temperature was maintained for continuous reaction for 4 hours, and then naturally cooled to room temperature to obtain a micro-crosslinked structure interlocking fluid loss reducer.
[0043] It is speculated that the structure of the micro-crosslinked interlocking fluid loss additive of this embodiment is as follows:
[0044]
[0045] It can be seen that the three C=C bonds in triallylamine undergo copolymerization reaction with other polymerizable monomers, wherein the length of the chain segments between the crosslinking points is controlled by a molecular weight regulator, thereby generating a network copolymer type fluid loss additive having an interlocking micro-crosslinking structure.
[0046] Example 2
[0047] 58g of 2-acrylamido-2-methylpropanesulfonic acid and 12g of maleic anhydride were weighed and dissolved in 510g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 20g of N,N-diethylacrylamide, 10g of N-vinylcaprolactam and 1.5g of triallylamine were added and mixed evenly; 0.2g of mercaptoethanol, 0.1g of tetrasodium ethylenediaminetetraacetate and 0.8g of potassium persulfate were then added to obtain a mixed system; the mixed system was heated to 50°C under stirring conditions of 200 rpm, and 0.37g of sodium sulfite was dissolved in 50g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 50°C over 40min. After the addition was completed, the temperature was slowly raised to 75°C and maintained at this temperature for continuous reaction for 3h, and then naturally cooled to room temperature to obtain a micro-crosslinked structure interlocking fluid loss reducer.
[0048] Example 3
[0049] 55 g of 2-acrylamido-2-methylpropanesulfonic acid and 5 g of itaconic acid were weighed and dissolved in 680 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 25 g of N-hydroxyethyl acrylamide, 15 g of N-vinyl caprolactam and 0.5 g of pentaerythritol tetraallyl ether were added and mixed evenly; 3 g of isopropanol, 0.5 g of disodium ethylenediaminetetraacetate and 1 g of azobisisobutyramidine hydrochloride were then added to obtain a mixed system; the mixed system was heated to 55° C. under stirring conditions of 150 rpm, and 0.56 g of ferrous sulfate was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 55° C. over 60 minutes. After the addition was completed, the temperature was slowly raised to 80° C. and the temperature was maintained for continuous reaction for 5 hours, and then naturally cooled to room temperature to obtain a micro-crosslinked structure interlocking fluid loss additive.
[0050] Example 4
[0051] 37g of 2-acrylamido-2-methylpropanesulfonic acid, 5g of maleic acid and 10g of fumaric acid were weighed and dissolved in 750g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 28g of diacetone acrylamide, 20g of vinyl cyclopentane and 2g of triallylamine were added and mixed evenly; 1.5g of 2-mercaptobenzoic acid, 1.5g of diethylenetriaminepentaacetic acid and 0.6g of benzoyl peroxide were then added to obtain a mixed system; the mixed system was heated to 60°C under stirring at 100 rpm, and 0.3g of N,N-dimethylaniline was dissolved in 50g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 60°C over 30min. After the addition was completed, the temperature was slowly raised to 65°C and the temperature was maintained for continuous reaction for 6h, and then naturally cooled to room temperature to obtain a micro-crosslinked structure interlocking fluid loss reducer.
[0052] Example 5
[0053] 67 g of 2-acrylamido-2-methylpropanesulfonic acid, 4 g of itaconic acid and 4 g of acrylic acid were weighed and dissolved in 250 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 15 g of N-isopropylacrylamide, 10 g of N-vinylcaprolactam and 0.5 g of pentaerythritol tetraallyl ether were added and mixed evenly; 0.8 g of mercaptopropionic acid, 1.2 g of diethylenetriaminepentaacetic acid and 0.3 g of isopropylbenzene hydroperoxide were then added to obtain a mixed system; the mixed system was heated to 50° C. under stirring conditions of 150 rpm, and 0.35 g of sodium dithionite was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 50° C. over 50 minutes. After the addition was completed, the temperature was slowly raised to 75° C. and the temperature was maintained for continuous reaction for 2 hours, and then naturally cooled to room temperature to obtain a micro-crosslinked structure interlocking fluid loss reducer.
[0054] Example 6
[0055] 64 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of maleic anhydride and 4 g of acrylic acid were weighed and dissolved in 350 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 15 g of N-n-butoxymethyl acrylamide, 5 g of vinyl cyclopentane and 1 g of triallylamine were added and mixed evenly; 0.05 g of mercaptopropionic acid, 0.1 g of disodium ethylenediaminetetraacetate and 0.5 g of ammonium persulfate were then added to obtain a mixed system; the mixed system was heated to 40° C. under stirring conditions of 200 rpm, and 0.23 g of sodium bisulfite was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 40° C. over 60 minutes. After the addition was completed, the temperature was slowly raised to 70° C. and the temperature was maintained for continuous reaction for 4 hours, and then naturally cooled to room temperature to obtain a micro-crosslinked structure interlocking fluid loss reducer.
[0056] Comparative Example 1
[0057] 74 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of maleic anhydride and 4 g of acrylic acid were weighed and dissolved in 350 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 15 g of N-n-butoxymethyl acrylamide and 5 g of N-vinyl pyrrolidone were then added and mixed evenly; 0.05 g of mercaptopropionic acid, 0.05 g of disodium ethylenediaminetetraacetate and 0.5 g of ammonium persulfate were then added to obtain a mixed system; the mixed system was heated to 45° C. under stirring conditions of 200 rpm, and 0.23 g of sodium bisulfite was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 45° C. over 30 minutes, and after the addition was completed, the temperature was slowly raised to 70° C. and the temperature was maintained for continuous reaction for 4 hours, and then naturally cooled to room temperature to obtain a fluid loss reducer.
[0058] Comparative Example 2
[0059] 79g of 2-acrylamido-2-methylpropanesulfonic acid, 2g of maleic anhydride and 4g of acrylic acid were weighed and dissolved in 350g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 15g of N,N-dimethylacrylamide was then added and mixed evenly; 0.05g of disodium ethylenediaminetetraacetate and 0.5g of ammonium persulfate were then added to obtain a mixed system; the mixed system was heated to 45°C under stirring at 200 rpm, and 0.23g of sodium bisulfite was dissolved in 50g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 45°C over 30min. After the addition was completed, the temperature was slowly raised to 70°C and the temperature was maintained for continuous reaction for 4h, and then naturally cooled to room temperature to obtain a fluid loss reducer.
[0060] Comparative Example 3
[0061] 74 g of 2-acrylamido-2-methylpropanesulfonic acid was weighed and dissolved in 350 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 15 g of N-n-butoxymethylacrylamide, 5 g of N-vinylpyrrolidone and 1 g of triallylamine were added and mixed evenly; 0.05 g of mercaptopropionic acid, 0.05 g of disodium ethylenediaminetetraacetate and 0.5 g of ammonium persulfate were then added to obtain a mixed system; the mixed system was heated to 45° C. under stirring conditions of 200 rpm, and 0.23 g of sodium bisulfite was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 45° C. over 30 minutes, and after the addition was completed, the temperature was slowly raised to 70° C. and the temperature was maintained for continuous reaction for 4 hours, and then naturally cooled to room temperature to obtain a fluid loss reducer.
[0062] Comparative Example 4
[0063] 74 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of maleic anhydride and 4 g of acrylic acid were weighed and dissolved in 350 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 15 g of N-n-butoxymethyl acrylamide and 1 g of triallylamine were added and mixed evenly; 0.05 g of mercaptopropionic acid, 0.05 g of disodium ethylenediaminetetraacetate and 0.5 g of ammonium persulfate were then added to obtain a mixed system; the mixed system was heated to 45° C. under stirring conditions of 200 rpm, and 0.23 g of sodium bisulfite was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 45° C. over 30 minutes, and after the addition was completed, the temperature was slowly raised to 70° C. and the temperature was maintained for continuous reaction for 4 hours, and then naturally cooled to room temperature to obtain a fluid loss reducer.
[0064] Comparative Example 5
[0065] 74 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of maleic anhydride and 4 g of acrylic acid were weighed and dissolved in 350 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 15 g of acrylamide, 5 g of N-vinyl pyrrolidone and 1 g of N,N-methylenebisacrylamide were added and mixed evenly; then 0.05 g of mercaptopropionic acid, 0.05 g of disodium ethylenediaminetetraacetate and 0.5 g of ammonium persulfate were added to obtain a mixed system; the mixed system was heated to 45° C. under stirring conditions of 200 rpm, and 0.23 g of sodium bisulfite was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 45° C. over 30 minutes, and after the addition was completed, the temperature was slowly raised to 70° C. and the temperature was maintained for continuous reaction for 4 hours, and then naturally cooled to room temperature to obtain a fluid loss reducer.
[0066] Comparative Example 6
[0067] 74 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of maleic anhydride and 4 g of acrylic acid were weighed and dissolved in 350 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 15 g of N-n-butoxymethylacrylamide, 5 g of N-vinylpyrrolidone and 1 g of triallylamine were added and mixed evenly; then 0.5 g of ammonium persulfate was added to obtain a mixed system; the mixed system was heated to 45° C. under stirring conditions of 200 rpm, and 0.23 g of sodium bisulfite was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 45° C. over 30 minutes. After the addition was completed, the temperature was slowly raised to 70° C. and the temperature was maintained for continuous reaction for 4 hours, and then naturally cooled to room temperature to obtain a fluid loss reducer.
[0068] Comparative Example 7
[0069] 100 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of maleic anhydride and 4 g of acrylic acid were weighed and dissolved in 350 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 3 g of N-n-butoxymethyl acrylamide, 5 g of N-vinyl pyrrolidone and 1 g of triallylamine were added and mixed evenly; 0.05 g of mercaptopropionic acid, 0.05 g of disodium ethylenediaminetetraacetate and 0.5 g of ammonium persulfate were then added to obtain a mixed system; the mixed system was heated to 45° C. under stirring conditions of 200 rpm, and 0.23 g of sodium bisulfite was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 45° C. over 30 minutes, and after the addition was completed, the temperature was slowly raised to 70° C. and the temperature was maintained for continuous reaction for 4 hours, and then naturally cooled to room temperature to obtain a fluid loss reducer.
[0070] Comparative Example 8
[0071] 20 g of 2-acrylamido-2-methylpropanesulfonic acid, 2 g of maleic anhydride and 4 g of acrylic acid were weighed and dissolved in 350 g of water, and sodium hydroxide was slowly added to adjust the pH value of the system to 6-7; 15 g of N-n-butoxymethylacrylamide, 40 g of N-vinylpyrrolidone and 8 g of triallylamine were added and mixed evenly; 0.05 g of mercaptopropionic acid, 0.05 g of disodium ethylenediaminetetraacetate and 0.5 g of ammonium persulfate were then added to obtain a mixed system; the mixed system was heated to 45° C. under stirring conditions of 200 rpm, and 0.23 g of sodium bisulfite was dissolved in 50 g of water to prepare a reducing agent solution, and the reducing agent solution was slowly added dropwise to the mixed system at 45° C. over 30 minutes, and after the addition was completed, the temperature was slowly raised to 70° C. and the temperature was maintained for continuous reaction for 4 hours, and then naturally cooled to room temperature to obtain a fluid loss reducer.
[0072] Test Case
[0073] When the test temperature is less than 180°C, the performance of the fluid loss additive is evaluated according to the methods described in GB / T 19139-2012 "Test methods for oil well cement" and SY / T 5504.2-2013 "Evaluation methods for oil well cement admixtures Part 2: fluid loss additives". When the test temperature is greater than or equal to 180°C, the fluid loss performance evaluation method of the fluid loss reducer is as follows: the cement slurry system mixed with the fluid loss reducer is placed in the slurry cup of the high-temperature and high-pressure thickener, and after the thickening test steps in the above standard are installed, the temperature is raised to the corresponding test temperature and test pressure within the set time, and after constant temperature and constant pressure maintenance for 30 minutes, the temperature is lowered to about 90°C, the cement slurry system is removed, and the oil on the top of the cement slurry system is removed; then the cement slurry system is stirred evenly with a constant speed agitator, and then placed in the preheated high-temperature and high-pressure fluid loss instrument slurry barrel, and after the operation in the above standard is installed, the temperature is slowly raised to the corresponding test temperature, and the pressure difference between the top pressure of the slurry barrel and the bottom condenser is ensured to be 6.9MPa; after reaching the test temperature, a water loss test is carried out, and the water loss in 30 minutes is recorded. The API water loss of the cement slurry system is twice the water loss in 30 minutes.
[0074] The cement slurry system formula at the experimental temperature of 20-90°C is: 600g G-grade oil well cement (HSR) + x% fluid loss additive + (44-x)% water.
[0075] The cement slurry system formula for the experimental temperature of 120-150℃ is as follows: 600g G-grade oil well cement (HSR) + x% fluid loss reducer + 35% quartz sand (200 mesh) + 0.6% high temperature stabilizer DRK-3S + 1% dispersant DRS-1S + 2% ultra-high temperature retarder DRH-3L + 0.5% defoamer DRX-1L + (55-x)% water. The density of the cement slurry system is 1.90g / cm 3 .
[0076] The cement slurry system formula for the experimental temperature of 180-200℃ is as follows: 500g G-grade oil well cement (HSR) + x% fluid loss reducer + 50% quartz sand (200 mesh) + 1% high temperature stabilizer DRK-3S + 3% ultra-high temperature suspension stabilizer DRK-4L + 2% dispersant DRS-1S + 3% ultra-high temperature retarder DRH-3L + 0.5% defoamer DRX-1L + (60-x)% water. The density of the cement slurry system is 1.90g / cm 3 .
[0077] The cement slurry system formula for the experimental temperature of 220-245℃ is as follows: 500g G-grade oil well cement (HSR) + x% fluid loss reducer + 70% quartz sand (200 mesh) + 1% high temperature stabilizer DRK-3S + 3% ultra-high temperature suspension stabilizer DRK-4L + 2% dispersant DRS-1S + 5% ultra-high temperature retarder DRH-3L + 0.5% defoamer DRX-1L + 10% high temperature strength decay inhibitor DRB-3S + (70-x)% water. The density of the cement slurry system is 1.90g / cm 3 .
[0078] It should be noted that the percentage (%) in the above cement slurry system formula represents the mass percentage of each material in the G-grade oil well cement, that is, the mass of the G-grade oil well cement is 100% and the proportion of each material. The amount of fluid loss reducer in the above cement slurry system is shown in Table 1. In addition, the water in the above cement slurry system formula is fresh water or saturated salt water (i.e., 36% NaCl aqueous solution), as shown in Table 1.
[0079] The comprehensive performance evaluation results of the fluid loss reducers prepared in the above examples and comparative examples are shown in Table 1.
[0080] Table 1
[0081]
[0082]
[0083] In Table 1, “*” represents the mass concentration in water, and “—” represents not measured.
[0084] It can be seen from Table 1 that, as the experimental temperature increases, the API water loss of the cement slurry system with the same formula containing the fluid loss reducer of the embodiment of the present invention changes less, and the temperature resistance of the fluid loss reducer of the embodiment of the present invention reaches 245°C, and it is resistant to saturated brine. When the experimental temperature is 20-150°C, the API water loss of the cement slurry system mixed with 3% of the fluid loss reducer prepared in Example 1 of the present invention can be controlled below 50mL, and the sedimentation stability is good, there is no free liquid, and the 24h cement stone compressive strength is high. When the experimental temperature is 180-245°C, by appropriately increasing the dosage of the fluid loss reducer, the API water loss of the cement slurry system can also be reduced to below 50mL, and the cement slurry ash time does not exceed 30s, which can meet the on-site mixing requirements. In addition, as the experimental temperature increases, the density difference of the cement slurry system increases slightly, but the sedimentation stability (i.e., density difference) can be controlled at 0.03 / cm 3 Below, and there is no free liquid, and there is no adverse effect on the mechanical strength of high-temperature cement paste. Under 245°C and saturated brine conditions, the API water loss of the cement slurry system added with 5% of the fluid loss reducer of Example 1 of the present invention is also less than 50mL. At the same time, under 245°C, the API water loss, ash removal time, sedimentation stability and mechanical strength of cement paste of the cement slurry system added with the fluid loss reducers of Examples 1-6 of the present invention are all high.
[0085] In addition, compared with Comparative Example 1, the fluid loss reduction performance, sedimentation stability and cement stone compressive strength of the cement slurry system mixed with the fluid loss reducer prepared in Example 1 of the present invention at 90°C are not much different from those of Comparative Example 1; however, the various properties of the fresh water and saturated salt water cement slurry systems mixed with the fluid loss reducer prepared in Example 1 of the present invention at 245°C are much better than those of Comparative Example 1, indicating that the micro-cross-linked interlocking type fluid loss reducer of the present invention has a superior molecular structure and has excellent fluid loss reduction performance, sedimentation stability and ultra-high temperature and salt resistance.
[0086] The fluid loss reducer prepared in Comparative Example 2 is a typical linear anionic polymer. At 90° C., the performance difference between it and the fluid loss reducer prepared in Example 1 of the present invention is not large. However, at 245° C., the freshwater cement slurry system mixed with the fluid loss reducer prepared in Comparative Example 2 has a large API water loss, poor sedimentation stability, and a great influence on the compressive strength of the cement paste. The water loss of the salt water cement slurry system is uncontrollable, and other properties are further reduced.
[0087] The difference between Comparative Example 3 and Example 1 is that the vinyl-containing carboxylic acid or its derivative monomer is omitted; the difference between Comparative Example 4 and Example 1 is that the vinyl cyclic monomer is omitted; the difference between Comparative Example 5 and Example 1 is that N-n-butoxymethyl acrylamide is replaced by acrylamide, and the cross-linking agent is replaced by N,N-methylenebisacrylamide; the difference between Comparative Example 6 and Example 1 is that the molecular weight regulator and chelating agent are omitted; Comparative Examples 7 and 8 are that the dosage ratio of certain monomers or cross-linking agents in Example 1 is adjusted to outside the scope of the present invention. It can be seen that the fluid loss reducers of Comparative Examples 3-8 have problems such as large API water loss, poor sedimentation stability, and great influence on the compressive strength of cement paste under the condition of 245°C, and the thickening curve is bulging.
[0088] Figure 1 The effect of different curing times on the API water loss of cement slurry systems (fresh water) added with 5% of the fluid loss reducer prepared in Example 1 and 5% of the fluid loss reducer prepared in Comparative Example 1 at 245°C and 130MPa is shown. Figure 1 It can be seen that the water loss of the cement slurry system mixed with Example 1 changes less with the curing time, and the API water loss of the cement slurry system within the time range of 245°C curing for 10 hours is less than 50mL, indicating that its molecular structure and performance are stable under ultra-high temperature conditions, and it can meet the ultra-deep and ultra-deep well cementing technical requirements of ultra-high temperature and ultra-long cementing operation time. However, the water loss of the cement slurry system mixed with Comparative Example 1 gradually increases with the extension of curing time. The API water loss of the cement slurry system cured at 245°C for 2 hours is greater than 100mL, and the water loss is greater in the later period, which seriously affects the comprehensive performance and construction safety of the ultra-deep and ultra-deep well ultra-high temperature cementing cement slurry system.
[0089] Figure 2 The effect of different salt concentrations on the API water loss of the cement slurry system mixed with the fluid loss reducer prepared in Example 1 under the conditions of 245°C and 130MPa is shown. Figure 2 It can be seen that the water loss of the cement slurry system added with 4% of Example 1 tends to gradually increase with the increase of salt concentration, but the API water loss of the saturated salt water system is still less than 100 mL; the water loss of the cement slurry system added with 5% of Example 1 is less affected by the salt concentration, and the API water loss of the saturated salt water cement slurry system can be controlled below 50 mL, indicating that the fluid loss reducer prepared in Example 1 of the present invention has strong ultra-high temperature and salt resistance.
[0090] Figure 3 The thickening curve of the cement slurry system containing 4% of the fluid loss reducer prepared in Example 1 at 245°C and 130 MPa is shown. Figure 3It can be seen that under ultra-high temperature and high pressure conditions, the thickening curve of the cement slurry system is normal, and there is no abnormal fluctuation in temperature and pressure. The initial consistency of the system is 15Bc, and the consistency changes slightly with the increase in temperature, and finally maintains at about 11Bc, and the thickening time of the cement slurry system is 450min. This shows that the fluid loss reducer has basically no adverse effects on the initial flow state, high temperature sedimentation stability and thickening performance of the cement slurry system.
[0091] In summary, the micro-crosslinked interlocking fluid loss agent of the present invention has excellent heat resistance, pressure resistance and salt resistance, and the heat resistance and pressure resistance can reach 245°C and 130MPa, and the salt resistance can reach saturation; and the water loss reduction performance is excellent; and the sedimentation stability of the cement slurry system under ultra-high temperature conditions and the mechanical properties of cement stone can be significantly improved; at the same time, it has basically no adverse effect on the thickening performance of the cement slurry system, and the thickening curve is normal; and the applicable temperature range is wide, and it is applicable in the temperature range of 20-245°C. Therefore, the micro-crosslinked interlocking fluid loss agent of the present invention has excellent comprehensive performance, which can overcome the defects of the polymer-based fluid loss agent in the prior art, such as poor heat resistance and salt resistance, strong high-temperature dilution, poor sedimentation stability of the cement slurry system, "inverted" thickening time, and great influence on the mechanical strength of cement stone, and has good application prospects in the cementing fields such as deep wells, ultra-deep wells, extra-deep wells, high-pressure gas wells, unconventional oil and gas wells, gas storage wells and geothermal wells.
[0092] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a micro-crosslinked interlocking fluid loss additive, comprising the following steps: (1) 30-90 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid, 3-20 parts by weight of a carboxylic acid or its derivative monomer containing a vinyl group, and water are mixed, and a pH adjuster is added to adjust the pH value of the system to 6-7; 5-30 parts by weight of a modified acrylamide monomer, 2-30 parts by weight of a vinyl cyclic monomer, and 0.1-3 parts by weight of a crosslinking agent are added, wherein the crosslinking agent includes a compound containing three alkenyl groups or four alkenyl groups; and then 0.02-3 parts by weight of a molecular weight regulator, 0.05-2 parts by weight of a chelating agent, and 0.2-1 parts by weight of an oxidant are added to obtain a mixed system; (2) adding an aqueous solution containing 0.2-1 parts by weight of a reducing agent dropwise into the mixed system, and reacting for a period of time after the addition is completed to obtain the micro-crosslinked interlocking fluid loss additive.
2. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: The weight ratio of the 2-acrylamido-2-methylpropanesulfonic acid, the vinyl-containing carboxylic acid or its derivative monomer, the modified acrylamide monomer, the vinyl cyclic monomer, the crosslinking agent, the molecular weight regulator, the chelating agent, the oxidizing agent and the reducing agent is (37-74): (5-15): (15-28): (5-20): (0.5-2): (0.05-3): (0.05-1.5): (0.3-1): (0.23-0.56).
3. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (1), the vinyl-containing carboxylic acid or its derivative monomer comprises one or more of acrylic acid, itaconic acid, maleic anhydride, maleic acid and fumaric acid.
4. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (1), the amount of water used is 230-850 parts by weight based on 30-90 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid.
5. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (1), the modified acrylamide monomer includes one or more of N-n-butoxymethyl acrylamide, N,N-diethyl acrylamide, N-hydroxyethyl acrylamide, diacetone acrylamide and N-isopropyl acrylamide.
6. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (1), the vinyl cyclic monomer includes one or more of N-vinyl pyrrolidone, N-vinyl caprolactam and vinyl cyclopentane.
7. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (1), the cross-linking agent includes one or both of triallylamine and pentaerythritol tetraallyl ether.
8. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (1), the molecular weight regulator includes one or more of mercaptopropionic acid, mercaptoethanol, isopropanol, dodecanethiol, hydroquinone and 2-mercaptobenzoic acid.
9. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (1), the chelating agent includes one or more of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate and diethylenetriaminepentaacetic acid.
10. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (1), the oxidant includes one or more of ammonium persulfate, potassium persulfate, azobisisobutylimidazoline hydrochloride, azobisisobutylamidine hydrochloride, hydrogen peroxide, benzoyl peroxide and isopropylbenzene hydroperoxide.
11. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (2), before the aqueous solution containing 0.2-1 parts by weight of the reducing agent is added dropwise to the mixed system, the method further comprises: heating the mixed system to 30-60° C. under stirring conditions of 150±50 rpm.
12. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (2), the reducing agent includes one or more of sodium sulfite, sodium bisulfite, ferrous sulfate, ferrous chloride, N,N-dimethylaniline and sodium dithionite.
13. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (2), the dripping time is 30-60 min, and the temperature of the mixed system during the dripping process is 30-60°C.
14. The method for preparing the micro-crosslinked interlocking fluid loss additive according to claim 1, wherein: In step (2), the reaction temperature is 60-90° C., and the reaction time is 1-6 h.
15. A micro-crosslinked interlocking fluid loss additive, prepared by the preparation method of the micro-crosslinked interlocking fluid loss additive according to any one of claims 1 to 14.
16. A cementing slurry system, the cementing slurry system comprising at least: Cement, and the micro-crosslinked structure interlocking fluid loss additive as claimed in claim 15.
17. The cementing slurry system according to claim 16, wherein: The cementing slurry system comprises: 100 parts by weight of cement, 3-5 parts by weight of the micro-crosslinked structure interlocking fluid loss reducer, 0-80 parts by weight of quartz sand, 0-6 parts by weight of stabilizer, 0-3 parts by weight of dispersant, 0-6 parts by weight of retarder, 0-0.5 parts by weight of defoamer, 0-15 parts by weight of high temperature strength decay inhibitor and 40-70 parts by weight of water.
18. The cementing slurry system according to claim 16, wherein: The density of the cementing slurry system is 1.90±0.02 g / cm 3 .
Citation Information
Patent Citations
Inorganic-organic polymer oil well cement filtrate loss reduction additive, and preparation method and application thereof
CN109503782A
High-temperature-resistant salt-resistant polymer filtrate reducer used in water-based drilling fluid and preparation method thereof
CN104388061A
Preparation method of micro-crosslinked-structure high-temperature-resistant salt-resistant well cementing cement slurry filtrate loss reducer
CN106188395A
Salt-resistant low-temperature early-strength fluid loss agent and preparation method thereof
CN115850579A
Salt-resistant water-indispersible material for oil well cement and preparation method of salt-resistant water-indispersible material
CN117946328A
Cited By
Micro-crosslinked interlocking fluid loss reducer and preparation method therefor, and cement slurry system for well cementing
WO2026113687A1